Dynamic PID based approach for preventing DDOS attack in IP network - Vinutha Yadav, D; Nagaraj, J (International Journal of Computer Sciences and Engineering, 2019)
One of the most common attack known as DDOS(distributed denial-of-service) attack are threat to the net. In DDOS attack the intruder makes use of scattered zombies in order to transfer a huge quantity of traffic to the targeted host, so that the legal users will not be able to access the network services or resources. The main cause for this attack to happen is the use of static PID’s, as this static PID’s remain constant throughout the session the intruder can easily trap these PID’s used and launch the DDOS attack. In order to overcome this problem, here in this project work we plan, estimate and evaluate the use of dynamic PID. Here we make use of 16 characters pseudorandom dynamic PID’s . In dynamic mode these PID’s keep on changing throughout the session , this makes hard for the intruders to track the PID’s and launch the attack.